Inflammatory Stimuli Significantly Change the miRNA Profile of Human Adipose-Derived Stem Cells - Zicheng Wang; Haili Li; Li Cheng; Zhongyuan Zhang; Hao Wang; Tongde Lv; Jian Lin; Liqun Zhou (Hindawi Limited, 2018)
Background. Human adipose-derived stem cells (hASCs) have been shown to have immunoregulatory properties in many studies. However, the mechanisms remain unknown. miRNAs are associated with many cellular processes, including immune responses. Thus, we hypothesized that miRNAs act as immunoregulators when hASCs are stimulated by inflammatory environments. Methods. A set of cytokines was used to stimulate the hASCs in the cytokine group, while no cytokines were used to stimulate the cells in the normal group. A microarray was used to obtain the miRNA expression profile of hASCs, and RT-PCR was used to validate the miRNAs that were differentially expressed between the two groups. Target genes were predicted using online databases, and KEGG analysis was performed to identify the pathways enriched by the target genes of all the differentially expressed miRNAs. Results. Five miRNAs were significantly upregulated, and 2 miRNAs were downregulated in the cytokine group compared with the normal group. We identified several immune-related pathways that are targeted individually or collectively by those miRNAs. Conclusion. Inflammatory stimuli changed the miRNA expression profile of hASCs. miRNAs may play a pivotal role in the immune response in hASCs and may be targets through which the immunoregulatory functions of hASCs can be enhanced.